Some Characterizations of Hopf Group on Fuzzy Topological Spaces - Demiralp, S.; Guner, E. (University of Sistan and Baluchestan, 2014)
In this paper, some fundamental concepts are given relating to fuzzy topological spaces. Then it is shown that there is a contravariant functor from the category of the pointed fuzzy topological spaces to the category of groups and homomorphisms. Also the fuzzy topological spaces which are Hopf spaces are investigated and it is shown that a pointed fuzzy toplogical space having the same homotopy type as an Hopf group is itself an Hopf group.
Keywords: 13. Climate action; 11. Sustainability